PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPOSISI DENGAN BERBANTU MEDIA AUDIO VISUAL - Sihombing, Novita Asmi; Sastromiharjo, Andoyo; Abidin, Yunus (Universitas Hamzanwadi, 2022)
This research is motivated by the low ability to write exposition texts of students in learning Indonesian. This is due to the use of learning media that is still less varied. This study aims to improve the ability to write exposition texts of students with the help of audio-visual media. The research method used in this study is a quantitative research method with an experimental approach. The type of experiment in this study is a quasi-experimental (quasi-experimental) with one group pretest-posttest design. The population in this study were students of class X SMA Negeri 3 Bangko Pusako Riau registered for the 2020/2021 school year with a total of 162 students. The research sample is class X IPA I as many as 34 people obtained by purposive sampling technique. The instrument used is an exposition text writing skill performance test with three indicators, namely the structure of the exposition text, the use of Indonesian spelling, and the function of the expository text. The data collected were analyzed by the teacher giving scores of the results of the exposition text writing skills test based on predetermined indicators. The results showed that the use of audiovidual media can improve the ability to write expository texts, both in terms of process and results. In the process, the improvement is seen in the learning process that is getting better and more enjoyable. As a result, the increase in learning outcomes can be seen from the average grade obtained.